العلاقة بين الدوافع للتعلم ومهارة الكلام لدى طلاب المعهد العصري - Wael Ali Al-Sayyid; Irfan Nur Alfil Lail (Department of Arabic Education - Faculty of Educational Sciences, 2022)
This study aims to reveal the correlation between motivation and speaking skills. This research uses descriptive quantitative approach and correlation method using the Product Moment Correlation formula. The data was collected using observation and distributing questionnaires. The sample of this research is 30 students. After the researchers distributed a questionnaire, the results obtained were 3.7 (74) with the predicate